Adoption of Target Costing in South African Higher Education: - Thango, Thobelani Sabelo; Nzuza, Zwelihle Wiseman; Marimuthu, Ferina (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study explores the factors influencing the adoption of target costing by higher education institutions in South Africa, along with the potential implications for pricing strategies. Design/methodology/approach: Conducted at a selected South African HEI, the research adopts a quantitative approach, utilizing both closed-ended and open-ended questions in a questionnaire survey targeting 52 heads of departments and 15 finance staff members. Findings: The findings reveal that institution size, data management system adequacy, staff collaboration, support, resource availability, lack of expertise, and sector competition significantly impact the delay and rejection of target costing adoption. This study enriches the existing body of knowledge by identifying barriers to the successful implementation of target costing in higher education, suggesting ways for its advanced application in the sector and beyond. Practical implications: This research contributes valuable insights for improving cost management and pricing strategies within HEIs, offering implications for policy and decision-making in the education sector. Paper type: Research Paper